Work-Family Conflict and Primary and Secondary School Principals’ Work Engagement: A Moderated Mediation Model - Yang, Zhongping; Qi, Shisan; Zeng, Lianping; Han, Xiaohong; Pan, Yun (Frontiers in Psychology, 2021)
With the development of positive psychology, work engagement has received widespread attention from researchers in the fields of positive organizational behavior and occupational health. Some studies have shown that work-family conflict has an important influence on individual behaviors and attitudes, but little research has studied the influence of work-family conflict on work engagement. The present study examined whether the relationship between work-family conflict and work engagement was mediated by job satisfaction, and whether the mediating role was moderated by affective commitment. We surveyed 358 Chinese primary and secondary school principals using the Work-Family Conflict Scale, Job Satisfaction Scale, Affective Commitment Scale, and Work Engagement Scale. The results revealed that there is a significant negative correlation between work-family conflict and primary and secondary school principals’ work engagement, and this relationship was partially mediated by job satisfaction. Moreover, affective commitment played a moderating role in the relationship between job satisfaction and work engagement. Specifically, the relationship between job satisfaction and work engagement was significant for primary and secondary school principals with high and low affective commitment. The current study contributes to a better understanding of the relationship between work-family conflict and work engagement.